EFEKTIVITAS SIM DALAM MENINGKATKAN KINERJA PENGELOLA WISATA RIAU - Aziz, Andi Abdul; Iskandar, Iskandar (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
Abstract: This study aims to analyze the effectiveness of management information systems in improving the performance of tourism object managers in Riau Province. This research method is quantitative descriptive. This study was conducted by conducting a survey of 100 tourism object managers in Riau Province, using a purposive sampling method. The collection of research data used a questionnaire with a Likert scale, and the data analysis technique used simple linear regression analysis. The results of the study showed that the SIM obtained a t-count greater than the t-table (10.637> 2.023). Thus, it can be concluded that the SIM variable has a positive and significant influence on the performance of tourism object managers in Riau Province. Keywords: Management Information Systems, Performance